Efficacy of Fumigants for Control of Sal Seed and Seedling Borer Pammene theristis Meyrick (Lepidoptera: Tortricidae) - Sharma, Manisha; Singh, K. P.; Pandey, Kamal (Indian Forester, 2022)
Sal (Shorea robusta Gaertn.) is one of the most important timber species of Indian sub-continent. Along with timber, Sal seeds are of great commercial importance. The quality of seed production and seed viability are affected by insect infestation on tree stands and during storage which causes considerable economic loss. Pammene theristis Meyrick is the most destructive pest, which bores both the seeds and seedlings of Sal. Fumigation is an effective management method of suffocating or poisoning the seed borers within the seed and thus controlling the infestation. A laboratory study was carried out in Insectary, Forest Research Institute, Dehradun. The results revealed that the most effective fumigant against the seed borer P. theristis was found to be EDB + CCl4 at 0.2 ml/kg dose for 48 hours. It was followed by EDB (at 0.2 ml/kg), PDCB (at 0.2 ml/kg) and CS2 (at 0.2 ml/kg) at 48 hours duration each.